Biological control of Puto barberi (Hemiptera: Putoidae) with Orius insidiosus (Hemiptera: Anthocoridae) ex situ - Schoeneck López, Carlos Max (2024)
This study evaluated the predatory capacity of Orius insidiosus on the mealybug Puto barberi on the campus of the University of Guayaquil, due to the presence of serious phytosanitary problems caused by this insect. Specimens of Orius insidiosus were collected for three months from a nursery at the Vinces Support Center, Los Ríos province, while mealybugs were obtained from ornamental plants (Ixora coccinea) in the green areas of the Ciudadela Universitaria. Trials were established using ½ liter plastic containers with sweet potato cuttings as refuge for O. insidiosus and Ixora coccinea cuttings for the mealybugs; to later introduce the predatory insects. Predation was evaluated at 24, 48 and 72 h. Statistical analysis showed no significant differences between treatments (p-value=0.65). However, it was observed that the percentage of predation accumulated by O. insidiosus (♀) was 31.5%, while for O. insidiosus (♂) it was 28.5%. It is concluded that O. insidiosus has potential as a biological controller of mealybugs, although it is recommended to validate these results under field conditions. In order to test the predatory capacity of O. insidious for mealybugs under controlled conditions.